Why don't donor countries coordinate their aid? A case study of European donors in Morocco. (January 2016) - Olivié, Iliana; Pérez, Aitor
Lack of coordination among donors poses several problems: it results in higher administrative costs for both donors and partner countries and weakens aid effectiveness. This rationale is the basis for the OECD and EU political agendas on harmonization and coordination, which has resulted in different coordination initiatives at both headquarters and field levels. However, despite the political agenda, recent studies show that for many donors and partner countries aid fragmentation has prevailed or even increased. By means of a country case study in Morocco, this document explores the obstacles to aid coordination in a specific EU development partner country. Coordination initiatives may have proliferated but not necessarily triggered results in terms of joint work or donors' specialization. The main obstacles to coordination include varied administrative procedures; diverse administrative architectures; resistance from local authorities and also from leading donors (to abandon or share flagship aid programmes).